Chemoradiation-Induced Superior Vena Cava Syndrome: A Case Report. Issue 8 (2008) - Castonguay, Mathieu; Rodrigues, George; Vincent, Mark; Malthaner, Richard A; Guo, Lin-Ruo
Abstract : A case of a 54-year-old man who developed superior vena cava syndrome secondary to vascular fibrosis, 30 months after radical chemoradiation for stage III non-small cell lung cancer, is presented. The literature regarding the etiology, diagnosis and treatment of this rare entity is discussed.